ECONOMIC INDICATORS OF SURGICAL TREATMENT OF ATHEROSCLEROSIS OF THE FEMORAL-POPLITEAL SEGMENT IN PATIENTS FOR CRITICAL LIMB ISHEMIA - O.A. Holyachenko; Y.M. Gupalo; O.I. Nabolotnuy; B.L. Kulikovskuy; A.V. Shamrai-Sas; A.O. Golyachenko; A.M. Kucyn (Клінічна та профілактична медицина, 2021)
Introduction: is to analyze the economic indicators of different types of surgical treatment of atherosclerosis of the femoral-popliteal segment of the lower extremity in patients for сritacal limb ishemia.